남성 독거노인의 삶의 질 예측모형 - 김수진; 전경숙; Kim, Su Jin; Jeon, Gyeong-Suk (Journal of Korean Academy of Nursing, 2020)
Purpose: This study aimed to construct and test a predictive model that explains and predicts the quality of life in older men living alone. Methods: A self-report questionnaire was used to collect data from 334 older adult men living along aged 65 years or over living in Jeollanam-do provinces. The endogenous variables were depression, self-rated health, instrumental activity of daily life, health promotion behaviors, the number of social participation activities and quality of life. Data were analyzed using the SPSS 21.0 and AMOS 21.0 programs. Results: The final model with 14 of the 8 analysed paths showed a good fit to the empirical data: χ2 = 173.26(p < .001, df = 53), normed χ2 = 3.27, GFI = .92, NFI = .90, CFI = .93, TLI = .89, RMSEA = .08 and SRMR = .06. Activities had direct effect on quality of life of older men living alone and social support had both direct and indirect effects. Meanwhile, function and socioeconomic status showed only indirect effects. The variables included in the eight significant paths explained 83.7% of variance in the prediction model. Conclusion: Instrumental activities of daily living and social support effect directly on quality of life in the older men living alone. Findings suggest that health care providers including community nurses need to provide social support as well as empowerment programs of instrumental activities of daily living and health promotion for improving quality of life of the older men living alone.